D-dimer levels in predicting the severity of acute pancreatitis - M. S., Anil Kumar; Kothagattu, Ranjith (International Surgery Journal, 2017)
Background:Coagulative disorder is known to occur in the early phase of acute pancreatitis. (AP) and D-dimer is a commonly used clinical parameter of haemostasis. The aim of this study was to assess the value of the plasma D-dimer level as a marker of severity in the 1.3.5 days after admission in patients with Acute pancreatitis. Methods: From September 2015 to September 2017, 60 patients admitted for AP were included in this observational study. The D-dimer level was measured during days 1,3,5 after admission and the acute physiology and chronic health evaluation (APACHE) II score, sequential organ failure assessment (SOFA) score, and other clinical parameters were recorded at the same time. The maximum and the mean D-dimer values were used for analysis and compared with other prognostic factors of AP. Results:Both the maximum and mean levels of D-dimer were signiﬁcantly different between patients with and without clinical variables such as multiple-organ dysfunction syndrome (MODS), need for surgical intervention, and the mortality. Additionally, the D-dimer level correlated well with two usual markers of AP severity-the APACHE II score and the C-reactive protein level. Conclusion D-dimer measurement is a useful, easy, and inexpensive early prognostic marker of the evolution and complications of AP. Conclusions:D-dimer measurement is a useful, easy, and inexpensive early prognostic marker of the evolution and complications of SAP.